Factors Influencing Investor’s Perception Towards Mutual Funds In Tamil Nadu: A Study - SELVAN, Dr. S.C.B. SAMUEL ANBU; G, Mr RAMRAJ (The journal of contemporary issues in business and government, 2021)
In India, retail investors generally depend on the information that provides neither inflation hedges nor positive absolute returns. Millions of investors have acquired new insights thanks to mutual funds, which have taken investment to their doorstep. A mutual fund is an investment vehicle that pools money from several different investors and invests it in stocks, shares, short-term money market instruments, other securities or properties, or a combination of these. The primary motivation for investing in mutual funds is to earn a decent return with low risk. As a result, mutual fund success is largely the result of skilled fund managers' combined efforts and diligent investors. It is critical to understand mutual fund investors' needs and their preferences for mutual fund schemes, and their performance assessment in the current environment. This research aims to examine how investors in Tamil Nadu perceive mutual funds as an investment choice. A survey of over a hundred professional Tamilnadu investors is currently underway. A structured questionnaire was used to collect data, and descriptive statistical methods such as demographic analysis with simple percentages, rotation component matrix, and ANOVA test were used to analyze it. According to the results, age and marital status have no impact on investors' perceptions of mutual funds. Furthermore, factors such as benefits, Convenience, and reputation influence investors' purchasing behaviour. The research would benefit academics, market researchers, institutional investors, traders, distributors, and other potential investors.